Micromorphology of third ventricular ependyma in Catla catla (Ham.) - Mondal, B; Rath, S C (Indian Journal of Fisheries, 2011)
The micromorphology of the ependymal cells, lining the third ventricle of thebrain ot Catla catla (Ham.) are studied and reported. The findings are comparedwith that of 'ovaprim' injected and bred individuals. Third ventricle of catla isbordered with ependymal cells of varied shape and size. Cells are usuallyspherical, columnar or spindle shaped. Tanycytes bear single or multiple basalprocess. The apical process may bear ciliated structure or are projected as broadend feet to the ventricle. Supra ependymal cells are common. The ventricle of theinduced bred brood bears plenty of PAS, AB, and AF positive secretory colloidwhereas little secretory material or no secretory material is found in the controlindividuals. Golgi-Cox positive ependymal tanycytes are found all along theventricle. Tanycytes are closely associated with the blood vessels and other neuralcomponents. Spider cells are often found in the sub-ependymal layer. The dendritesof liquor contacting neurons and apical process of ependymal cells of 'ovaprim'induced bred catla show very distinct Golgi-Cox positive secretory materialsprojecting into the ventricle. The lumen of the ventricle of the same also containGolgi-Cox positive deposition in contrast to the non-induced fish.